Autovalores e autovetores: significação do Estudo das vibrações - Amorim, Layane Silva de (Universidade Federal Rural do Semi-Árido, 2017)
The vibrations are more present in our daily lives than we can imagine. Note-If your presence in construction, human body, musical instruments and among other places. Seeking to verify the presence of the concepts of eigenvalues and eigenvectors in the study of this phenomenon, the work had as main objective to identify whether the features of linear algebra that supports the development of computational tools integrated a theoretical minimum required to engineer. For this, an analysis of eight semantics works, being these, project report, completion of course work, dissertation and thesis, based on the Model of Semantic Fields created by professor Romulo Campos Lins. It was concluded that, of the eight works, six are the data obtained in their productions and justify by means of the meanings inherent in the concepts of linear algebra used in preparation of computational tools, reflecting the need for this disc.
Eigenvalues ​​and eigenvectors: significance of the study of vibrations
Keywords: Frequência natural; Modo de vibração; Autovalor; Autovetor; Significação; Natural frequency; Vibration mode; Eigenvalue; Eigenvector; Signification; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA